Opposition in International Law – Alternativity and Revisibility as Elements of a Legitimacy Concept for Public International Law. (30th October 2015) - LEY, ISABELLE
Abstract: As international law is widening in regulatory scope and intensity, it arguably suffers from a legitimacy deficit. This article conceives of this deficit as a deficit in possibilities to politicize, criticize, and contest international law-making proposals in the way a loyal opposition does in a domestic constitutional context: through the representation of relevant societal interests, the voicing of critique, and the safeguarding of alternative proposals for the future. The author of this article tries to bring together the current debate in political theory on the value of legitimate disagreement and dissent in political institutions and the ongoing discussion on the legitimacy of international law. Therefore, a concept of an institutionalized opposition for international law-making processes is developed, referencing authors such as Hannah Arendt and Claude Lefort. Next, the author analyses whether one can already find instances of an institutionalized opposition in international law – in parliamentary assemblies and in international agreements which are designed to present a legal–political counterweight to specific legal concepts and institutions.